Risky responsibilities for rural drinking water institutions: The case of unregulated self-supply in Bangladesh. (November 2020) - Fischer, Alex; Hope, Rob; Manandhar, Achut; Hoque, Sonia; Foster, Tim; Hakim, Adnan; Islam, Md. Sirajul; Bradley, David
Highlights: Up to 9 million unregulated tubewells were privately installed in Bangladesh since 2006. Rural households experienced a threefold decline in real costs of tubewells since 1982. Households' financed MDG advances towards improved rural drinking water access. Unmonitored self-supply is risky but new preferences create opportunities for regulated services. Achieving SDG 6.1 implies transition from provision of access to risk-management models. Abstract: The drinking water sector is off track to reach Sustainable Development Goal (SDG) 6.1 with over a quarter of the world's population lacking safe and reliable services. Policy approaches are shifting away from provision of access towards managing the multiple risks of water supply and quality. By considering how infrastructure, information, and institutional systems evolved in Bangladesh, this article identifies the unintentional consequences of reallocating management responsibility for rural water services away from government agencies towards individuals and households. Between 2012 and 2017, we estimate up to forty-five unregulated tubewells were installed privately for every publicly funded rural waterpoint. This growth rate more than doubled total national waterpoint infrastructure since 2006. The scale of growth is reflected in the declining ratio of households per tubewell from over fifty-seven in 1982 to less than two in 2017, potentially approaching market saturation. This scale of growth aligns to an observed decrease in the real price of private market shallow tubewells by seventy percent between 1982 and 2017. In 2018, we estimate households invested up to USD253 million in tubewells, nearly sixty-five percent of the total national water and sanitation sector's household-level finance. In effect, household investments became critical to achieve the Millennium Development Goal (MDG) target of improved infrastructure access, but now pose challenges for meeting targets of safely managed services. The scale of continued private investment provides an opportunity for policymakers to explore blended public finance models to meet emerging consumer preferences, while at the same time introducing regulatory and monitoring systems.